Are Patients Traveling for Intraoperative Radiation Therapy? - Kelsey E. Larson; Stephanie A. Valente; Chirag Shah; Rahul D. Tendulkar; Sheen Cherian; Courtney Yanda; Chao Tu; Jessica Echle; Stephen R. Grobmyer (International Journal of Breast Cancer)
Purpose. One benefit of intraoperative radiation therapy (IORT) is that it usually requires a single treatment, thus potentially eliminating distance as a barrier to receipt of whole breast irradiation. The aim of this study was to evaluate the distance traveled by IORT patients at our institution. Methods. Our institutional prospective registry was used to identify IORT patients from 10/2011 to 2/2017. Patient’s home zip code was compared to institution zip code to determine travel distance. Characteristics of local (<50 miles), regional (50–100 miles), and faraway (>100 miles) patients were compared. Results. 150 were patients included with a median travel distance of 27 miles and mean travel distance of 121 miles. Most were local (68.7%), with the second largest group living faraway (20.0%). Subset analysis of local patients demonstrated 20.4% traveled <10 miles, 34.0% traveled 10–20 miles, and 45.6% traveled 20–50 miles. Six patients traveled >1000 miles. The local, regional, and faraway patients did not differ with respect to age, race, tumor characteristics, or whole breast irradiation. Conclusions. Breast cancer patients are traveling for IORT, with 63% traveling >20 miles for care. IORT is an excellent strategy to promote breast conservation in selected patients, particularly those who live remote from a radiation facility.